Investigation of Causal Factors Is Disshort Arabic Language Lessons - Halimah; Wilita, Irza; Badriyah, Laelatul; Aprillia, Lola (International Journal of Education and Teaching Zone, 2023)
This study will discuss the problems faced by students while learning Arabic at Madrasah Aliyah Al-Huda. This type of research is descriptive qualitative. In this study, data were collected through observation, interviews, and documentation. This study aims to find out why many students of Madrasah Aliyah Al-Huda are not happy in learning Arabic. The research subjects totaled 63 students. Including 46 male studentns and 17 female students with a sample of 5 students, using a simple random sampling method. The results of this study indicate that there are 4 factors, namely : The difficulty in translating into Indonesian, the lack of learning media, the lack of basic Arabic because the schools are diverse (from public schools), and environmental factors that are not conducive.